Wykorzystanie optymalnego sterowania do prognozowania zjawisk gospodarczych - Kaźmierska-Zatoń, Maria M.; Zatoń, Wojciech (The Use of Optimal Control for Forecasting in the Economy, 2006)
Optimal control problem in the economics leads to the choice of the optimal economic policy from the set of the alternatives. In other words, the problem is to find such policy instruments that enable to realize assumed control objectives with the minimum loss (the difference between the optimal values from the solution and desirable levels). The economic system to be controlled is usually described by the mathematical model (an econometric model in particular). The optimal control model may be used as a tool for forecasting. In this case we forecast values of the exogenous variables (some of them selected as instruments) not endogenous ones (now being control objectives) as in the usual approach. When modelling macroeconomy the instruments may be: tax rate, budget expenses, or central bank interest rate, the objectives: production, consumption, unemployment rate or a level of inflation. In a model for an enterprise we could select wages, products' prices, research and development expenses, marketing expenses (instruments) and sales, profit, return on equity, market share, financial liquidity ratio or a debt ratio (objectives). In the paper we describe the specific use of optimal control for forecasting purposes and show some results based on a small econometric model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 219-227